Application of the Differentiated Learning Model of Independent Curriculum in Improving Learning Outcomes - Assirri, Ryya Aulia (Jurnal Pijar Mipa, 2025)
One important aspect of the Independent Curriculum is differentiated learning, which recognizes individual differences in students and provides learning experiences that are tailored to their needs and interests. This article will analyze the application of differentiated learning models to improve student learning outcomes in essential materials of elementary school science subjects. This research is a quantitative descriptive study, using the method Independent Samples T-Test, consisting of experimental classes and conventional classes to see if there are differences in learning outcomes using a differentiated learning model..Based on the results of the data analysis, a significance value of 0.000 was obtained, because this significance value is much smaller than 0.05, it can be concluded that there is a significant difference between the two groups being compared. These results show that there is a difference in learning outcomes using a differentiated model according to the characteristics of essential material in the Independent Curriculum, namely, the flexibility of learning in the classroom. Differentiated learning is an important strategy in responding to today's educational challenges to meet the unique needs and potential of each student.